Spring equinox festival in the Mountainous Badakhshan Autonomous Region of Tajikistan: Ethnolinguistic analysis and interlinear glossing of a Shughnani text - Edelman, J. I.; Dodykhudoeva, L. R. (ИАЭ)
The article presents a narrative written by R.Kh. Dodykhudoev for a children’s reading primer in the Shughnani language intended to teach reading skills to the young generation of school children, monolingual speakers of their native languages. The text contains the description of the New Year holiday – Nowruz, as it was celebrated in the mid-20th century in the Mountainous Badakhshan Autonomous Region of Tajikistan, and details the particular festive customs associated with the younger generation. This Shughnani narrative (presented with interlinear glossing) forms a contribution to the corpus of texts in the Shughnani language, which, like other Pamir languages, lacked a written tradition until recently. В статье представлен повествовательный текст, подготовленный Р. Х. Додыхудоевым для «Букваря шугнанского языка», разработанного для обучения чтению в начальной в школе детей, владеющих только родным шугнанским языком. В тексте дается описание празднования в середине ХХ века Нового Года – Навруза – в Горно-Бадахшанской автономной области Таджикистана, обычаев, связанных с интересами подрастающего поколения. Этот шугнанский текст, приведенный с поморфемной нотацией, является вкладом в корпус письменных текстов на шугнанском языке, который, как и прочие памирские языки, до недавнего времени не имел письменной традиции.
Keywords: Ethnography